Structural optimization method based on cellular automata simulation - Toyoda, Tetsuya; Kita, Eisuke (Computer Assisted Methods in Engineering and Science, 2023)
This paper describes the topology and the shape optimization scheme of the continuum structures using the cellular automata simulation. The design domain is divided into small square cells. By considering the cells as the elements, the stress analysis of the structure is carried out by finite element method. Then, the design variables are updated according to the local rule and the stress distribution. The rule is defined as the simple relationship between a cell whose design variable is updated and its neighborhood cells. In this paper, we will discuss the formulation to analytically derive the rules from the optimization problems. The special constraint condition named as "CA-constraint condition" is introduced first and then, the global optimization problem for the whole structure is divided into the local problem for some neighboring cells. The derived rules are applied to the same numerical example in order to discuss the theoretical validity of the formulation and the feature of the rules.